Pelatihan dan pemberdayaan masyarakat dalam pembuatan Virgin Coconut Oil (VCO) - Sultan Hazanuddin; Saskia Aulia Ashar; Muhammad Aidil Ramadhan Syafruddin; Nur Abidah; Muhammad Adrian; Muh Ainul Fitrah; Andi Dihya; Baiduri Musfira Saad; Idawati; Hasna (P3HKI - Universitas Muhammadiyah Parepare, 2024)
Watang Bacukiki Village, Parepare, is rich in coconut trees. However, society has not fully utilized its economic potential and health benefits. This is caused by a lack of knowledge and skills in processing old coconuts and the perception that the process is complicated and requires high costs. Through instruction and mentoring, this service project seeks to improve the community's understanding of and proficiency in the conversion of aged coconuts into virgin coconut oil (VCO). The method used is a participatory and educational approach using lecture, discussion, demonstration, and mentoring techniques. The learning media used are handouts and videos. The community was very enthusiastic and knowledgeable about the principles and procedures involved in creating VCO. Additionally, the community now has more options to improve welfare and income thanks to this training. The community's knowledge and proficiency in turning old coconuts into VCO has increased as a result of this service project, which has also created new potential to improve welfare and revenue.